PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA TENAGA KEPENDIDIKAN DI UNIVERSITAS X - Mochamad Vrans Romi (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
Abstract. This study aimed to analyze the influence of leadership and organizational culture onperformance of educators at the Islamic University of Bandung. This study uses a quantitative methodwith descriptive analysis and verification. Data was collected by questionnaires. The sample in thisstudy 130 respondents. Analysis of the data used is path analysis. The results showed transformationalleadership and work environment at the X University included in the excellent category that influencemotivation education personnel in order to improve the quality of service and the impact that is good forthe performance of educators at the X University